The Influence Of Location, Product Completeness And Service Quality On Consumer Purchasing Decisions At Shop Enggano, Bengkulu City - M. Ferdiansyah; Eti Arini (Penerbit Jurnal Indonesia, 2023)
To determine the effect of location on purchasing decisions at Enggano Stores and determine the effect of product completeness on purchasing decisions at Enggano Stores. Quantitative research type. Data collection techniques are documentation, observation and questionnaires. Data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Location has a positive effect on the purchasing decision of the Enggano Department Store in Bengkulu City, thus the better the location, the higher the purchasing decision at the Enggano Department Store in Bengkulu City. The completeness of the product has a positive effect on the purchasing decision of the Enggano Department Store in the City of Bengkulu, thus the higher the completeness of the product, the greater the purchase decision for the Enggano Department Store in the City of Bengkulu. Service quality has a positive effect on p the higher the service quality, the higher the purchasing decision at the Enggano Department Store in Bengkulu City. Location, product completeness and service quality together show an influence on purchasing decisi urchasing decisions at the Enggano Department Store in Bengkulu City, thus ons.